Potential Therapeutic Compounds for Neurological Diseases in Lavender Oil Extract (Lavandula Angustifolia) - Natih, Made Agus Raditya (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Lavender oil (Lavandula angustifolia) is widely known for its soothing aromatherapy effects and diverse therapeutic benefits. The plant is rich in bioactive compounds—terpenes (linalool, limonene, triterpenes), linalyl acetate, alcohols, ketones, polyphenols, coumarin, sineol, and flavonoids—with linalool and linalyl acetate as the main components. The flower part is chosen for oil extraction because it contains the highest concentration of compounds. This literature review aims to identify the potential of lavender oil in the treatment of neurological diseases. Sources were taken from international journals indexed by Google Scholar, PubMed, and Scopus using the Publish or Perish program in the range of 2019–2024 with the keywords "aromatherapy" AND "neurological disorders" AND "lavender" AND "essential oils" AND "neurological diseases". Of the 78 articles identified, 47 were further reviewed and 12 met the inclusion criteria; The data is analyzed descriptively. Results showed that lavender oil has anxiolytic and antidepressant effects through modulation of GABA-A, SERT, and NMDA receptors; anti-inflammatory effect and regulation of glutamate receptors as well as inhibition of calcium channels; as well as anti-epileptic mechanisms through increased GABA inhibition, potassium current, and decreased sodium flow. Effectiveness has been reported in conditions such as anxiety, major depression, epilepsy, migraines, and Alzheimer's. In conclusion, lavender aromatherapy is effective for the therapy of neurological disorders thanks to the content of linalool and linalyl acetate. The implications of this study are as a reference for the development of methods and further research on the clinical potential of lavender oil in the treatment of neurological diseases.